Kesetaraan Gender dalam pengembangan Bimbel Enggon Sin_Au_Qu pada pendidikan non formal Gen-Y dan I-Gen - Dyah Puspita Indah Budi Sari Wulan; Nurleila Jum'ati; Hardo Wahyudi; Risca Ayu Rachmania; Lusy Nur Miftachul Jannah; Mochamad Syahrul Gunawan; Haris Priambodo (Ilmu Psikologi Universitas Yudharta Pasuruan, 2022)
The COVID-19 pandemic has had an impact on all aspects of life, including education. The Indonesian government implemented a Distance Learning policy that made Bimbel Enggon Sin_Au_Qu which is a non-formal education service provider institution adapt and experience an increase in demand for services so that management added tutors. With this development, it is necessary to analyze gender equality in Bimbel Enggon Sin_Au_Qu. The data used is secondary data with a quantitative descriptive approach. The analysis carried out gave results in the form of mapping an increase in the number of students including Gen-Y and I-Gen. In terms of the quantity of tutors at Enggon Sin_Au_Qu as many as 18 people, dominated by female tutors as much as 56% while the remaining 44% are male tutors. The greater quantity of female tutors cannot be separated psychologically from women playing a role in shaping and developing the personality of students. The general description of the data on the role of tutors on students is the role of female tutors by 39% in the development of Gen-Y and I-Gen in Enggon Sin_Au_Qu, while the role of male tutors is greater, namely 61%. Based on these data, there are more female tutors in quantity, but in terms of quality male tutors have a bigger role in the development of non-formal education for Bimbel Enggon Sin_Au_Qu. Thus, it can be concluded that gender equality is the key in developing the non-formal education business of Enggon Sin_Au_Qu.